2011
DOI: 10.1364/ol.36.004824
|View full text |Cite
|
Sign up to set email alerts
|

Surface nanoscale axial photonics: robust fabrication of high-quality-factor microresonators

Abstract: Recently introduced surface nanoscale axial photonics (SNAP) makes it possible to fabricate high-Q-factor microresonators and other photonic microdevices by dramatically small deformation of the optical fiber surface. To become a practical and robust technology, the SNAP platform requires methods enabling reproducible modification of the optical fiber radius at nanoscale. In this Letter, we demonstrate superaccurate fabrication of high-Q-factor microresonators by nanoscale modification of the optical fiber rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 19 publications
3
59
1
Order By: Relevance
“…This problem was solved in [32] using the IR (CO 2 laser) and UV (248 nm excimer laser) beam exposures. It has been shown that it is possible to fabricate coupled SNAP microresonators [32][33][34][35][36] and other devices [37] at the surface of an optical fiber with sub-angstrom precision. A general method of precise variation of the effective radius of an optical fiber is based on local annealing of the fiber surface performed with a CO 2 laser beam [ Figure 8(A)].…”
Section: Methods Of Fabrication Of Snap Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem was solved in [32] using the IR (CO 2 laser) and UV (248 nm excimer laser) beam exposures. It has been shown that it is possible to fabricate coupled SNAP microresonators [32][33][34][35][36] and other devices [37] at the surface of an optical fiber with sub-angstrom precision. A general method of precise variation of the effective radius of an optical fiber is based on local annealing of the fiber surface performed with a CO 2 laser beam [ Figure 8(A)].…”
Section: Methods Of Fabrication Of Snap Devicesmentioning
confidence: 99%
“…In particular, a series of coupled SNAP microresonators can be fabricated along the Ge-doped fiber by exposure to UV radiation through an amplitude mask as illustrated in Figure 8(B). This approach allows the fabrication of very long chains of couple microresonators with sub-angstrom precision [32,34]. A combination of methods for the local modification of photosensitive optical fiber radii exploiting both UV and CO 2 exposures has been also demonstrated [34].…”
Section: Methods Of Fabrication Of Snap Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the outstanding fabrication precision achieved in modern microphotonics, which is currently as small as a few nanometers [2,5], is still far beyond the precision required for practical applications [3,11]. Surface nanoscale axial photonics (SNAP) is a new fabrication platform which allows to fabricate photonic structures with an unprecedented subangstrom precision and ultralow loss [12][13][14]. SNAP structures are formed at the surface of an optical fiber with nanoscale effective radius variation (ERV).…”
mentioning
confidence: 99%
“…1). Recently several high performance micro-devices, such as coupled ring resonators [13] and bottle resonator delay lines [14], have been demonstrated based on the SNAP platform.SNAP structures are usually fabricated by local annealing of the fiber surface using a focused CO2 laser [12][13][14]. Annealing causes the local relaxation of the residual stress introduced during the fiber drawing process and leads to a nanoscale ERV of the fiber.…”
mentioning
confidence: 99%